(untitled) - Umland, Jean B (Minneapolis, 1993)
The book contains marginal comments in blue to signal the location of related material, to explain why a particular approach is used, to cite references to the chemical literature, and so forth. Most of these marginal notes are derived from the "dialogues" that were carried on between the reviews
Keywords: Chemistry